2011
DOI: 10.1074/jbc.m111.277046
|View full text |Cite
|
Sign up to set email alerts
|

Type II Arginine Methyltransferase PRMT5 Regulates Gene Expression of Inhibitors of Differentiation/DNA Binding Id2 and Id4 during Glial Cell Differentiation

Abstract: PRMT5 is a type II protein arginine methyltranferase that catalyzes monomethylation and symmetric dimethylation of arginine residues. PRMT5 is functionally involved in a variety of biological processes including embryo development and circadian clock regulation. However, the role of PRMT5 in oligodendrocyte differentiation and central nervous system myelination is unknown. Here we show that PRMT5 expression gradually increases throughout postnatal brain development, coinciding with the period of active myelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 46 publications
2
61
0
Order By: Relevance
“…In the present study, we found that PRMT1 plays a critical role in oligodendrocyte lineage progression. A previous study has shown that PRMT5 knockdown in C6 rat glioma cells and primary rat OPCs led to repressed maturation of oligodendrocyte, indicating that PRMT5 is important for oligodendrocyte differentiation (12). These studies suggest that both PRMT1 and PRMT5 positively regulate oligodendrocyte development.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the present study, we found that PRMT1 plays a critical role in oligodendrocyte lineage progression. A previous study has shown that PRMT5 knockdown in C6 rat glioma cells and primary rat OPCs led to repressed maturation of oligodendrocyte, indicating that PRMT5 is important for oligodendrocyte differentiation (12). These studies suggest that both PRMT1 and PRMT5 positively regulate oligodendrocyte development.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the distribution pattern of PRMT1 in mouse embryo has shown high expression in neural tube during embryonic stage (9). After birth, PRMT1 is still strongly expressed in the brain during the perinatal stage (12). It should be noted that PRMT5, the most characterized member of type II PRMTs that catalyze the monomethylation and symmetric dimethylation of proteins, also shows substantial expression in the brain (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the major PRMT catalyzing the SDMA modification of proteins, PRMT5 is involved in tumorigenesis via histone methylation and transcriptional gene silencing (39,40). Some nonhistone proteins are also directly methylated by PRMT5, resulting in tumor progression (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Glial cells such as oligodendrocytes are known to be regulated at multiple levels by epigenetics changes, including histone modifications and miRNAs (43,44). The expression of Ͼ37 miRNAs is regulated during oligodendrocyte differentiation (45).…”
Section: Discussionmentioning
confidence: 99%